Digitalization of Financial Management in the Practice of an International Chinese Company - Zhiwen Duan; Elena Egorycheva (Communications of International Proceedings, 2021)
Today, a large amount of information that a company receives in its activities must be systematized. It is the systematic accounting in the company that reveals the rational and effective ways of the company's development. The most important accounting is financial accounting, which contributes to the effective performance of financial managers and making the right decisions in the company's management strategy. The ability to use this information enables the company's management to work in a changing environment, benefit from the data obtained, and achieve higher performance indicators. Today, special information programs for financial accounting and reporting solve any global problems of any complexity. Today, such programs contain controls, methods of strategic financial analysis. Thanks to such information solutions, ways of achieving the set business goals in large companies and their divisions are identified. Therefore, today the process of digitalization of financial management plays a huge role. Financial management with the use of information technology significantly reduces the time for analysis, reduces costs and provides all the reports for making subsequent decisions. The purpose of the article is to study the digitalization of financial management in the practice of an international Chinese company. The methodological basis is general scientific methods of synthesis, analysis, structural analysis, systematization, classification, generalizations, induction and deduction, a method of comparative statistical and dynamic research.
Keywords: Financial management; competition; information technology; financial analysis; digitalization.